The Determinants of High School Students’ Entrepreneurial Intentions in Douala IV County: An Assessment through the Theory of Planned Behavior. - Kenmegni,; Mbonifor, (Archives of Business Research, 2021)
The purpose of this study is to examine the determinants of entrepreneurial intention among high school learners in Douala IV County, Cameroon. More precisely, the study aims to test whether the theory of planned behaviour can predict entrepreneurial intentions of high school learners in Douala IV County or not. In this vein, a cross-sectional survey was conducted using a sample of 300 pupils. The data collected are analysed through descriptive, correlation and regression analysis. It was found that a great majority of students intended to be self-employed in the future. Regression’s analysis showed that the personal attitude and perceived behavioral control have a positive and significant effect on high school students’ entrepreneurial intentions, while the subjective norms does not have. More so, the theory of planned behaviour is partially verified when high school students are concerned. A recommendation could be that the government should partner with media houses educating parents to stimulate entrepreneurship as a career choice among young people and develop an entrepreneurial culture in Cameroon. This study contributes to the body of entrepreneurship as it uses the theory of planned behavior in the context of high school students in a less developed country.